Resource‐Efficient Low‐Temperature Synthesis of Microcrystalline Pb2B5O9X (X = Cl, Br) for Surfaces Studies by Optical Second Harmonic Generation. Issue 23 (13th May 2020) - Tan, Deming; Kirbus, Benjamin; Rüsing, Michael; Pietsch, Tobias; Ruck, Michael; Eng, Lukas M.
Abstract: Optically nonlinear Pb2 B5 O9 X (X = Cl, Br) borate halides are an important group of materials for second harmonic generation (SHG). Additionally, they also possess excellent photocatalytic activity and stability in the process of dechlorination of chlorophenols, which are typical persistent organic pollutants. It would be of great interest to conduct in situ (photo‐) catalysis investigations during the whole photocatalytic process by SHG when considering them as photocatalytic materials. In order to get superior photocatalytic efficiency and maximum surface information, small particles are highly desired. Here, a low‐cost and fast synthesis route that allows growing microcrystalline optically nonlinear Pb2 B5 O9 X borate halides at large quantities is introduced. When applying the ionothermal growth process at temperatures between 130 and 170 °C, microcrystallites with an average size of about 1 µm precipitate with an orthorhombic hilgardite‐like borate halide structure. Thorough examinations using powder X‐ray diffraction and scanning electron microscopy, the Pb2 B5 O9 X microcrystals are indicated to be chemically pure and single‐phased. Besides, the Pb2 B5 O9 X borate halides' SHG efficiencies are confirmed using confocal SHG microscopy. The low‐temperature synthesis route thus makes these borate halides a highly desirable material for surface studies such as monitoring chemical reactions with picosecond time resolution and in situ (photo‐) catalysis investigations. Abstract : A resource‐efficient ionic‐liquid‐assisted, low‐temperature synthesis route of high‐quality Pb2 B5 O9 X (X = Cl, Br) borate‐halide microcrystallites is reported herein. Due to their finite size and large specific surface area, they exhibit excellent second harmonic conversion efficiencies. This is highly useful for surface studies, such as monitoring chemical reactions with picosecond time resolution, when investigating in situ (photo‐) catalysis, and for biological sensing.